Taxonomic study on the Chinese Steninae (Coleoptera, Staphylinidae), with descriptions of three new species of the Genus Stenus Latreille - Lv, Wei-Xiang; Zhao, Cai-Yun; Zhou, Hong-Zhang (Zootaxa, 2018)
This is a taxonomic study on the genus Stenus Latreille (Coleoptera, Staphylinidae) from China and includes descriptions of three new species: Stenus renjiafenicus Lv et Zhou, sp. nov., from Yunnan, Stenus longchishanicus Lv et Zhou, sp. nov., from Sichuan, and Stenus napoensis Lv et Zhou, sp. nov., from Guangxi, with illustrations and photos of the taxonomic characters. A latest key to all Chinese species of Stenus tenuimargo group is modified to include the new species. The following 4 Stenus species, S. feae Fauvel, 1895, S. claritarsis Puthz, 1971 S. malickyi Puthz, 2008, and S. iustus Puthz, 1976 are newly recorded to China and are redescribed, with illustrations and photos of the taxonomic characters.